Macroeconomic variables and stock prices in a small open economy: The case of Pakistan - Jahangir, Abbas (2010)
This paper is an attempt to determine empirically the relationship between the Karachi stock exchange and macroeconomic variables; discount rate (DR), inflation (CPI), industrial production (IPI), foreign exchange rate (FX Rate) and foreign exchange reserves (FX Res). The general objective of the study is to investigate the efficiency of the Karachi Stock Exchange as a semi strong market in light of the Efficient Market Hypothesis (EMH) over the period 1980 to 2007. Furthermore, we investigate the causal relationship between stock market returns and macroeconomic variables and determine how stock returns react to changes in macroeconomic variables. The results of the multivariate cointegration analysis show that economic growth and discount rate are inversely related to the stock market. Inflation on the other hand is positively related, while no relationship was found between foreign exchange reserves and foreign exchange rates. The Granger causality test shows that that a bi-directional relationship exists between stock prices and the MPI and causality running from discount rate to the Karachi stock exchange. We also find that the unexpected components of foreign exchange reserves and foreign exchange rates have a statistically significant impact on stock prices and that the market is informationally efficient in pricing stocks using news regarding the discount rate. Our overall conclusion for the Karachi stock exchange is that stock prices do not follow a random walk, all models that test the relationship between stock prices and macroeconomic variables must be used with caution and most importantly, the Karachi stock exchange cannot be used as a benchmark to gauge the overall performance and state of the economy.